Practicum Guidelines Development On Hormonal In Human Reproduction Material Of Class XI Of Senior High School With A Modified Open Inquiry Approach - Mimin Mardhiah Zural; Gusria Ningsih; Annika Maizelli; Nurhadi Nurhadi (Universitas Lambung Mangkurat, 2024)
The learning process on Hormone in Human Reproduction material of XI class of senior high school has employed Merdeka Curriculum. After the content of the Merdeka Curriculum book was analyzed, it was determined that the practicum activities were limited to hormones in the menstrual cycle and did not meet the requirements of phase F learning achievement. During practicum activities at school, teachers exclusively employ textbooks. The practicum guidelines in textbooks have not been able to comprehensively guide the students to complete the practicum activities, resulting in a lack of comprehension. The objective of this research was to generate a practicum guide that was valid, feasible, convenient, and effective. This research was a development study that employs the Plomp model (preliminary stage, prototype stage, and assessment stage). The validity test was assessed by three lecturers. The feasibility test was administered to three students with varying abilities (High, Moderate, Low), and six students were randomly selected. The practical guide convenience test was administered to one teacher and 45 students. The data was processed using a modified percentage formula from Ridwan (2013). The validity value was 88.68% (very valid), the feasibility test for three students was 96.11% (very feasible), and the feasibility of six students was 89.58% (very feasible). The convenience test administered by the teacher yielded results of 98.5% (very easy) and 84.34% students (very easy). The effectiveness for skill test yielded results of 81.14% (very effective) and the effectiveness for attitude yielded 91% (very effective), which were processed using the modified percentage formula from Sudijono (2006). Thus, the practicum guide developed for hormone material in human reproduction of XI class of senior high school is valid, feasible, convenient, and effective in the use of the learning process.